Surgical Management and Reconstruction Training (SMART) Course for International Orthopedic Surgeons - Hao-Hua Wu (Ubiquity Press, 2016)
Background The burden of complex orthopedic trauma in low- and middle-income countries (LMICs) is exacerbated by soft-tissue injuries, which can often lead to amputations. This study's purpose was to create and evaluate the Surgical Management and Reconstruction Training (SMART) course to help orthopedic surgeons from LMICs manage soft-tissue defects and reduce the rate of amputations. Methods In this prospective observational study, orthopedic surgeons from LMICs were recruited to attend a 2-day SMART course taught by plastic surgery faculty in San Francisco. Before the course, participants were asked to assess the burden of soft-tissue injury and amputation encountered at their respective sites of practice. A survey was then given immediately and 1-year postcourse to evaluate the quality of instructional materials and the course's effect in reducing the burden of amputation, respectively. Results Fifty-one practicing orthopedic surgeons from 25 countries attended the course. No participant reported previously attempting a flap reconstruction procedure to treat a soft-tissue defect. Before the course, participants cumulatively reported 580-970 amputations performed annually as a result of soft-tissue defects. Immediately after the course, participants rated the quality and effectiveness of training materials to be a mean of ≥4.4 on a Likert scale of 5 (Excellent) in all 14 instructional criteria. Of the 34 (66.7%) orthopedic surgeons who completed the 1-year postcourse survey, 34 (100%, 'P' < 0.01) reported performing flaps learned at the course to treat soft-tissue defects. Flap procedures prevented 116 patients from undergoing amputation; 554 (93.3%) of the cumulative 594 flaps performed by participants 1 year after the course were reported to be successful. Ninety-seven percent of course participants taught flap reconstruction techniques to colleagues or residents, and a self-reported estimate of 28 other surgeons undertook flap reconstruction as a result of information dissemination by 1 year postcourse. Conclusion The SMART Course can give orthopedic surgeons in LMICs the skills and knowledge to successfully perform flaps, reducing the self-reported incidence of amputations. Course participants were able to disseminate flap reconstructive techniques to colleagues at their home institution. While this course offers a collaborative, sustainable approach to reduce global surgical disparities in amputation, future investigation into the viability of teaching the SMART course in LMICs is warranted.